2007
DOI: 10.1097/01.ta.0000240962.62319.c8
|View full text |Cite
|
Sign up to set email alerts
|

Small Volume Resuscitation: A Randomized Controlled Trial With Either Norepinephrine or Vasopressin During Severe Hemorrhage

Abstract: AVP was comparable to NE with respect to hemodynamics and blood gases, as well as brain metabolism in surviving animals throughout the study period. Our findings emphasize the importance of early resuscitation, as neuronal cell damage potentially starts immediately after onset of severe hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Our study does not support the notional benefit (or at least non-harm) of AVP in hemorrhagic shock shown in previous investigations. 7,[13][14][15]17 However, AVP was only used in combination with other agents in our series. Therefore, the increased mortality with AVP was likely due to the interaction with the use of multiple drugs than this agent's close association with death as an independent or causative variable.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our study does not support the notional benefit (or at least non-harm) of AVP in hemorrhagic shock shown in previous investigations. 7,[13][14][15]17 However, AVP was only used in combination with other agents in our series. Therefore, the increased mortality with AVP was likely due to the interaction with the use of multiple drugs than this agent's close association with death as an independent or causative variable.…”
Section: Discussionmentioning
confidence: 92%
“…The concept of pharmacologic support in hemorrhagic shock has been substantiated to a greater degree in laboratory studies 7,9,14,18 versus clinical series. 4,8,11,15,16 Much of the promising human data are relegated to case reports.…”
Section: Discussionmentioning
confidence: 99%
“…In the porcine model of uncontrolled hemorrhagic shock, vasopressin, unlike epinephrine or saline placebo, ensured short-term survival (18,19). However, in another porcine model of hemorrhagic shock that was performed to compare norepinephrine with vasopressin, norepinephrine was comparable to arginine vasopressin with respect to cerebral perfusion pressure and brain metabolism (20). In the current study, we chose norepinephrine as a vasopressor rather than vasopressin because hemorrhagic shock causes myocardial depression and norepinephrine has been shown to increase cardiac index and myocardial performance (21)(22)(23).…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, we chose norepinephrine as a vasopressor rather than vasopressin because hemorrhagic shock causes myocardial depression and norepinephrine has been shown to increase cardiac index and myocardial performance (21)(22)(23). Moreover, norepinephrine increases cerebral perfusion pressure immediately after hemorrhagic shock (20,24).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies support the notion that AVP can increase tissue perfusion and oxygen delivery. For example, Meybohm et al reported that during hemodynamics decompensation, AVP infusion significantly increased the cerebral perfusion pressure and cerebral venous partial pressure of oxygen as compared with NE after 10 min of therapy (27). Taken together, AVP may be recommended as the first-line antishock agent at the early stage for some chronic cardiovascular diseases when subjected to hemorrhagic shock.…”
Section: Figmentioning
confidence: 96%